Relationship between drugs consumption and condom use - Marcel Elipe-Miravet; Rafael Ballester-Arnal; Cristina Giménez-García; Verónica Cervigón-Carrasco; María Dolores Gil-Llario (INFAD, 2019)
In the last years, there has been a rebound in sexually transmitted infections (STIs). Traditionally, STIs were associated with certain groups. However, it is observed that this accentuation occurs in different population groups due to risky sexual behaviours that are carried out, which are exacerbated by certain factors, such as toxic substance consumption, low risk perception and sexual sensations searching. The main goal is to verify the relationship between drugs consumption and condom use in different sexual practices. As secondary objectives, these same relationships will be studied according to the participant’s sex, as well as their sexual orientation. There were 1910 participants (733 men and 1177 women), who completed a survey about sexual experience and practices. The age average was 21,42 (SD = 5,54). Of these subjects, 1700 (89%) were considered heterosexual, 146 (7.6%) bisexual and 64 (3.4%) homosexual. On one hand, the results indicate that women who have consumed alcohol use less condom in vaginal sex practice than those who have not consumed (p= ,023). On the other hand, men use condoms less frequently if they have consumed hashish (p = ,021). In addition, if men consume cocaine, they do not use condoms in practices such as vaginal sex (p= ,035) or with sporadic sexual partners (p= ,007). Furthermore, heterosexual people who consume hashishuse less prophylactics in vaginal sex (p= ,006) and with sporadic sexual partners (p=,03). Hetero also use less condoms in vaginal sex (p= ,019) and with sporadic sexual partners (p= ,023) if they consume cocaine. Finally, bisexual people who consume alcohol use fewer condoms in vaginal sex (p= ,029). No differences were found between drugs and condom use in homosexuals. Despite the great amount of information about sexual health, which is principally taught at schools and high schools, it is a fact that young population carries out risky sexual behaviours. These risky behaviors are increased if there is a drug use. Future programs focused on sexual health should add the relationship between sex and drugs, in order to reduce STIs and increasing condom use.